Case Report: Xenogeneic mesenchymal stem cell secretome for the treatment of feline chronic gingivostomatitis - Almendros, Angel; Nekouei, Omid; Moores, Claudia; Jesky, Robert; Baiker, Kerstin; Tse, May (Frontiers in Veterinary Science, 2025)
This case series describes the treatment of eight cats with mesenchymal stem cell (MSC) secretome, a therapeutic modality never used before for refractory feline chronic gingivostomatitis (FCGS). The cats were free of systemic illness and were not on immunomodulators during treatment. All cats received two to three treatments of MSC secretome through intramucosal injections given 3 months apart. White cell count and globulins, stomatitis disease activity index (SDAI), and histopathology were used pre- and post-treatment to assess the response to treatment. Of the eight selected cases, resolution of clinical signs and significant improvement of lesions were reported in two cats. Six cats did not have a substantial clinical response, and lesions remained mostly unchanged. Six cats had a reduction in globulins, and five cats increased in weight, respectively, after treatment. SDAI decreased in all the cats treated. The two cats that had resolution of clinical signs had the most significant decrease in serum globulins and SDAI, and both increased in weight. No adverse effects or chemistry and hematological abnormalities directly associated with the use of MSC secretome were observed in any of the cats, suggesting human-derived MSC secretome can be safely used in cats. Increases in weight and reductions in SDAI and globulinaemia were observed in a subset of cats after treatment, suggesting an immunomodulatory effect and downregulation of proinflammatory factors. Well-designed clinical trials are recommended to verify the observed effects in this study and to evaluate long-lasting clinical benefits or potential side effects of the treatment.